HUBUNGAN STATUS GIZI, ANEMIA DAN PARITAS TERHADAP BERAT BAYI LAHIR DI KECAMATAN SEMAMPIR KOTA SURABAYA TAHUN 2016 - Rizkie Ayu Wahyunda (The Indonesian Journal of Public Health, 2019)
Birth weight is a measurement for the baby an hour after birth, and it is categorized into three types. They are low birth weight (<2500 gram), normal birth weight (2500-4000 gram), and obese birth weight (>4000 gram). According to the Ministry of Health of Indonesia, low birth weight could be at risk of death, disorder of growth and development. This research aimed to determine the correlation between nutritional status, anemia and parity to birth weight in Semampir sub-district of Surabaya city in 2016. It was an observational study with cross sectional design. The data used were secondary data about birth weight as dependent variable, whereas nutritional status, anemia and parity as independent variables. The result of Pearson’s linier correlation test showed that on one hand, there was a significant correlation between nutritional status, anemia and parity to birth weight with p-value = 0,017 and 0,000. On the other hand, there was no correlation between anemia and birth weight (p = 0,857). The conclusion was mother with normal nutritional status and mother with no risk of parity between 2 – 4 times were mostly delivering babies in normal birth weight.